Pengaruh PDB, Nilai Tukar dan Jumlah Uang Beredar Terhadap Inflasi di Indonesia Periode 1993-2012 - Sipayung, Putri Tirta Enistin; Kembar Sri Budhi, Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 7, Juli 2013 (pp. 314-349), 2013)
One of the problemsInalmost all countries inthe worldis the difficulty of maintaining the stability of the economy . Policies, both fiscal policy and monetary policy carefully planned and then carried out to obtain a variety of targets expected positive economic growth and bring prosperity to the community. One of the efforts the fulfillment of economic growth through inflation control, both at regional and national level. The inflation rate in the right figure is able to bring the economy towards positive growth. This study was conducted to determine the effect of the Gross Domestic Product(GDP), exchange rate and money supply on inflation rate in Indonesia. Results showed simultaneous Gross Domestic Product (GDP), the exchange rate and the money supply affect the inflation rate in Indonesia during 1993-2012 with F value of 8,911 and sig value 0.00, the value of Adjusted R square=0,555, which means 55,5 percent fluctuation rise and fall of the inflation rate in Indonesia is influenced by the Gross Domestic Product (GDP), the exchange rate and the money supply, while the remaining 44,4 percentis influenced by other variables not included in the model.
Keywords: Gross Domestic Product; exchange rate; money supply; inflation